The efficacy of intravitreal triamcinolone versus aser photocoagulation in the primary treament of diabetic macular oedema - Mustafa, Norlaili (2008)
Objective: To compare the efficacy and safety of intravitreal triamcinolone injection to laser photocoagulation in the primary treatment of diabetic macular oedema. Methodology: Forty patients with newly diagnosed diabetic macular oedema were randomized into 2 groups 20 in 4mg intravitreal triamcinolone acetonide (IVT A) injection of and 20 in laser photocoagulation group. Evaluation was done at three months and the macular oedema was quantified using HRT II. Intraocular pressure elevation, lenticular opacity and endophthalmitis were observed. Results: Mean visual acuity for IVTA group was 0.935(0.223) at baseline and 0.405(0.223) at three months, p<0.01. Mean visual acuity for laser group was 0.795(0.315) at baseline and 0.525(0.289) at three months, p<0.01. However, there was no statistically significant difference between the two groups, p=0.151. Mean macular oedema index for IVTA group was 2.539 (0.914) at baseline and 1.753 (0.577) at three months, p<0.01. Mean macular oedema index for laser group was 2.139 (0.577) at baseline and 1.711(0.472) at three months, p<0.01. However, there was no statistically significant difference between the two groups (p=0.811 ). The mean intraocular pressure was statistically significant pre and post IVT A injection (p=0.032). There was no significant cataract progression at three months in both groups, p=0.688 and no incidence of endophthalmitis post IVT A injection at three months review. Conclusion: Both IVT A and laser photocoagulation demonstrate good outcome as primary treatment in diabetic macular oedema patients. The IVTA is a relatively safe procedure.